Consortium of Bacillus sp. BTH22 and Trichoderma sp. to Control Bacterial Leaf Blight Disease in Rice Plants - Dwirizki Permata, Aprilla Hendiana; Purnawati, Arika; Prasetyawati, Endang Triwahyu (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2025)
Rice is a major food commodity in Indonesia that is currently experiencing a decline in production due to several factors, one of which is bacterial leaf blight (BLB) caused by the bacterium Xanthomonas sp. The use of chemicals in controlling this disease has many limitations, so alternatives are needed, such as antagonistic microbes. This study aims to evaluate the effectiveness of Bacillus sp. BTH22 and Trichoderma sp. individually and in consortium in suppressing BLB disease in rice plants in vitro and in vivo. The study was conducted at the Plant Health Laboratory of Universitas Pembangunan Nasional “Veteran” Jawa Timur and Green House of Kebun Bibit Wonorejo from March to June 2025. The methods used included in vitro diffusion well test and in vivo disease intensity observation with a completely randomized design consisting of 5 treatments, namely control and spraying of antagonistic microbes Bacillus sp. BTH22 and Trichoderma sp. alone or in consortium with 4 replicates. Data analysis used analysis of variance (ANOVA) and post-hoc HSD tests at a 5% significance level. The results show that the treatment with the Bacillus sp. BTH22 and Trichoderma sp. consortium was the most effective, with an inhibition zone of 13 mm, which is classified as strong, and the lowest disease intensity of 30.02% at 55 HST with a suppression rate of 69.98%. These results indicate that the consortium of the two antagonistic microorganisms has high potential as an effective and sustainable biological control agent for BLB based on the observed parameters of inhibition zone and disease attack intensity.